OPTIMASI PROSES PRODUKSI PAPAN PARTIKEL DARI AMPAS BIJI JARAK PAGAR (Jatropha curcas L.) - Fherdes Setiawan, Ika Amalia Kartika, Mohamad Yani, Dede Hermawan (Jurnal Teknologi Industri Pertanian, 2016)
Jatropha seed cake contained fiber and protein compounds that can be utilized as a biocomposite products such as particle board.The optimization of production process of particle board conducted with four factors : moisture content, steaming time, pressing temperature, and pressing time. The experimental design used central composite design (CCD) by using response surface method (RSM). Physical and mechanical properties (density, moisture content, water absorption, MOR and MOE) were tested with JIS A 5908-2003. The quality of particleboard from jatropha seed cake were density 0.88 – 1.15 g/cm3, moisture content 6.53 – 10.27%, water absorption at 2 hours 17 – 46%, water absorption at 24 hours 31 – 54%, MOR 36.2 – 275 kgf/cm2, and MOE 2200 – 14500kgf/cm2. The optimization models multi response was evaluated. The optimum of production process was obtained at moisture content 15%, steaming time 25 minutes, pressing temperature 180oC, and pressing time 8 minutes, where the quality of particleboard product were at moisture content 6.51%, water absorption at 24 hours 34.67%, MOR 275 kgf/cm2, and MOE 14600 kgf/cm2.Keywords : jatropha seed cake, particleboard, response surface method